ბერძენი პუბლიცისტები დამოუკიდებელი საქართველოს შესახებ (1919-1921) - გამრეკელი, თეა (ლოგოსი, 2025)
Greek-Georgian relations go back centuries. In addition to common religion and cultural values, the Greeks and Georgians were also united by an insatiable desire for freedom. They always sympathized with each other in the struggle for freedom. Georgia's declaration of independence in 1918 caused a great response in Greece. In 1919, the government of the First Democratic Republic of Georgia sent a delegation to Athens. This article analyzes the views expressed by Greek publicists of that era about Georgia, its independence, the visit of a Georgian governmental delegation to Greece, and Greek-Georgian relations. The newspaper articles express an extremely benevolent attitude towards Georgia. The support of Greece was very important for the young nation. Full translations or brief summaries of the articles written by Greek authors were also published in the Georgian press of that period. Finding and familiarizing ourselves with this material revealed the importance Greece attached to Georgia's independence, cooperation, and the future role of the young Democratic Republic in the international political arena.